Experimental and Numerical Study of the Strength Performance of Deep Beams with Perforated Thin Mild Steel Plates as Shear Reinforcement - Chai K.F.; Woon K.S.; Wong J.K.; Lim J.H.; Lee F.W.; Lee Y.L. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study aims to investigate a new shear reinforcement method which utilizes thin mild steel (TMS) plates as shear reinforcement in deep beams to replace conventional reinforcement. Thirteen reinforced concrete deep beam specimens with three different plate thicknesses and four varying perforated hole arrangements on the TMS plates were experimentally tested to determine the load-carrying capacity and crack pattern. The experimental results indicate that the 2.0 mm thick TMS plate has the highest load-carrying capacity. Among the four different hole arrangements on the TMS plates, the perforated plates with a three-column hole arrangement show the best performance in terms of load-carrying capacity, with a 2.9% increment against the control beam specimen. The specimens also demonstrated compatible elastic stiffness with the control beam that used conventional shear links. This shows that TMS plates have the potential to replace conventional shear links in deep beams. This proposed method also changed the failure mode from conventional diagonal shear tension failure to a combination of flexural failure and shear deformation. A numerical model was developed and was found to have a good correlation with the experimental results, demonstrating potential for use in future parametric investigations on deep beams and cost reduction in future experimental work. 2023 by the authors.